2014
DOI: 10.1016/j.jep.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of hydroethanolic extract of Helicteres sacarolha A. St.- Hil. et al.

Abstract: Our results confirmed that HEHs have a broad safety margin for therapeutic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 27 publications
0
24
0
2
Order By: Relevance
“…Relative organ weight is a reliable indicator which can be used to measure the degree of toxicity of any drugs or chemicals [38]. Our study demonstrated that in male rats, after administration of extract at different doses all organs increased mostly significantly except stomach which showed a decrease in weight, whereas in female rats only stomach and ovary showed decrease in their weight.…”
Section: Discussionmentioning
confidence: 56%
“…Relative organ weight is a reliable indicator which can be used to measure the degree of toxicity of any drugs or chemicals [38]. Our study demonstrated that in male rats, after administration of extract at different doses all organs increased mostly significantly except stomach which showed a decrease in weight, whereas in female rats only stomach and ovary showed decrease in their weight.…”
Section: Discussionmentioning
confidence: 56%
“…The antiurolithiatic property of this formulation makes it imperative to be used for a long period of time; hence there is a dire need to establish its safety profile. Acute toxicity is usually an initial study performed: to serve as the basis for classification and labeling, to provide initial information on the mode of toxic action of a substance, to help arrive at a dose of a new compound, to aid in the identification of the further range of doses in animal studies and also for calculating the therapeutic index of drugs and chemicals 31,33 . Administration of hydroalcoholic extract of majoon hajrul yahood in rats does not cause death.…”
Section: Discussionmentioning
confidence: 99%
“…The functional capacity of the kidney was evaluated via the determination of the serum urea and creatinine levels 1 . Clinical biochemistry tests are used in toxicology studies to generate data that are crucial for evaluating altered organ function or major toxic effects in tissues in experimental animals 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Mass of the organs is often used as a sensitive indicator for evaluating the toxic impact of different substances, including medical (Balogun et al, 2014;Varcholyak & Gutyi, 2019). Relative mass of the organs of animals following the diet with excessive content of fat changed both under the influence of alcohol and alcohol tincture of Aralia.…”
Section: Discussionmentioning
confidence: 99%